Information System for Price Comparison and Prescription Reading using Automation Technologies and Digitalization of Texts for Pharmacies in Peru - Kherlin Hijar Flores, Jesarela (2024)
The Peruvian population has problems with access to free medicines, as this leads to go to private pharmacies affecting the economy, since many of the prices of medicines are not accessible to the budget of the population, this leads to another problem which is the abandonment of treatment. Therefore, a technological solution is proposed that integrates web scraping and OCR (Optical Character Recognition) technology for the extraction of information from pharmacies with web pages, for the comparison of drug prices. The solution also scans prescriptions for a fast and accurate search. The solution aims to facilitate the drug search by saving time and money, as they will be able to visualize the compared prices and purchase the drug at a lower cost. The solution has been validated on 20 prescriptions, which has led to a positive result, with a prescription scanning accuracy of 90.5%. Likewise, with the solution a search can be performed in a time of 30.87 seconds and thus also obtain an economic saving of 8.16 soles in contrast to other pharmacies.